Respuesta :

Question is not complete and so I have attached the complete question.

Answer:

C: f(x) = -½x + 4

Step-by-step explanation:

Using slope formula between 2 points, we know that;

slope; m = (y2 - y1)/(x2 - x1)

Let's consider 2 points from the table;

(0, 4) and (-4, 6)

Thus;

m = (6 - 4)/(-4 - 0)

m = 2/-4

m = -½

Now using slope intercept form equation which is y - y1 = m(x - x1), we can find the equation of the function by picking on point say (0, 4).

Thus;

y - 4 = -½(x - 0)

y - 4 = -½x

y = -½x + 4

Thus;

f(x) = -½x + 4

Ver imagen AFOKE88